Accreditation of prior experiential learning in France: an evolving system with national characteristics - Méhaut, Philippe [Verfasser]; Lecourt, Anne-Juliette [Verfasser] (My University, 2010)
"The purpose of this article is to examine the French system of accreditation of prior experiential learning (APEL) in the light of experiences elsewhere in Europe. We shall do so by determining the extent to which the institutional characteristics of the system and the way in which it is put into practice reflect some of the main French societal characteristics of the training and certification system and its place in the labour market. However, we shall also consider the extent to which this new system departs from the traditional system and meets new socio-political and economic challenges. The article is based on a reading of the law and on the initial analyses and data available." (Autorenreferat, BIBB-Doku)
Keywords: L 2.1.3 Erfahrungslernen; S 2.2.4 Anrechnung, Prüfung & Zertifizierung; I 2.2.1 Westeuropa; Erfahrungsorientiertes Lernen; Anerkennung; Zertifizierung; Sozialpartner; Frankreich